2015
DOI: 10.1172/jci81061
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-30 family members regulate calcium/calcineurin signaling in podocytes

Abstract: Calcium/calcineurin signaling is critical for normal cellular physiology. Abnormalities in this pathway cause many diseases, including podocytopathy; therefore, understanding the mechanisms that underlie the regulation of calcium/calcineurin signaling is essential. Here, we showed that critical components of calcium/calcineurin signaling, including TRPC6, PPP3CA, PPP3CB, PPP3R1, and NFATC3, are the targets of the microRNA-30 family (miR-30s). We found that these 5 genes are highly expressed as mRNA, but the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(103 citation statements)
references
References 64 publications
5
96
0
Order By: Relevance
“…In the present study, we found CaN inhibitors (CsA and FK506) reduced the 24-h urinary protein and ameliorated the serum albumin, triglyceride, and cholesterol abnormalities in PAN-treated SD rats, as well as reducing the foot-process effacement and recovering the expression of podocyte cytoskeleton markers synaptopodin and podocin, implying that CsA and FK506 reduced proteinuria by protecting podocytes in PAN induced MCD model. Furthermore, in agreement with previous findings6262728, we also found that CsA and FK506 directly protect podocyte cytoskeleton and restore the expression of synaptopodin and podocin in cultured mouse podocytes. Moreover, podocyte functional assay also showed increased cell viability and decreased cell motility in CsA and FK506 preincubated podocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found CaN inhibitors (CsA and FK506) reduced the 24-h urinary protein and ameliorated the serum albumin, triglyceride, and cholesterol abnormalities in PAN-treated SD rats, as well as reducing the foot-process effacement and recovering the expression of podocyte cytoskeleton markers synaptopodin and podocin, implying that CsA and FK506 reduced proteinuria by protecting podocytes in PAN induced MCD model. Furthermore, in agreement with previous findings6262728, we also found that CsA and FK506 directly protect podocyte cytoskeleton and restore the expression of synaptopodin and podocin in cultured mouse podocytes. Moreover, podocyte functional assay also showed increased cell viability and decreased cell motility in CsA and FK506 preincubated podocytes.…”
Section: Discussionsupporting
confidence: 93%
“…miR-30c-5p was associated with proteinuria and cellular crescents in LN. The members of the miR-30 family are important regulators of podocyte homeostasis and pathogenesis abundantly expressed in the kidney where their deregulation is associated with podocyte injury as described in patients with primary focal segmental glomerulosclerosis (35, 36). Members of this family have a similar sequence, but their genes are localized on different chromosomes, making a different gene-expression pattern possible, depending on different stimuli (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is elevated in patients with FSGS and results in proteinuria, podocyte flattening and loss of foot process architecture in a mouse model . In addition, the miRNA‐30 family seems to be of importance, as it was described to be upregulated in several independent cohorts . Moreover, miR‐10 , miR‐125b, miR‐186 , miR‐192, miR‐205 , miR‐196a and miR‐490 seem to be promising candidates as markers in FSGS (Table ).…”
Section: Conclusion and Future Of Mirnas In Fsgsmentioning
confidence: 99%
“…Downstream cytoplasmic nuclear factor of activated T‐cell (NFATC) family members are dephosphorylated by activated calcineurin. In normal podocytes, the mRNA levels of TRPC6, PPP3CA, PPP3CB, PPP3R1 and NFATC3 are highly expressed but protein levels are low . In podocytes of PAN‐treated rats, the protein levels of these proteins were upregulated and this upregulation was prevented by exogenous miR‐30a or glucocorticoids .…”
Section: Podocytic Mirna Expression Highlights Regulatory Functions Omentioning
confidence: 99%